Light and sound in the verb shifts in Monodrama shows (Journal of the College of Basic Education, 2023)
The universe is originally dark and the light of the sun is the one that displaces this darkness and illuminates the universe. The sun is the main source of light and a source of life on Earth, and without it, that life would not have been possible on this planet.And the sense of visual perception in humans cannot see without light, so light is the basic condition for a person to visually perceive the world around him, and the average person gets 90% of most of the information that reaches him through sight, so it is a basic element for achieving the optical image, and the artistic form of the image depends on The extent of the use of light in the expression of action, so the researcher intended to enter the tagged title (contributions of light to action transformations in mondrama performances). The second chapter (theoretical framework) has included two sections, the first is the concept of light and is included in the visual criterion and the spiritual concept of light, and the second section includes the dramatic light structure, the function of light, and the light structure of the image. The fourth chapter discusses the researcher's results and conclusions and lists the sources and references.